EFFECT OF SOLUTION pH AND TEMPERATURE ON PHENOL ADSORPTION ONTO CARBONIZED RICE HUSK CHEMICALLY ACTIVATED WITH PHOSPHORIC ACID - YAHAYA S. MOHAMMAD; MOHAMMED U. GARBA; MUHAMMAD A. MUHAMMAD; YAKUBU AZEH; SULEIMAN Y. BAGIREI (Journal of Engineering Studies and Research)
Operating conditions such as pH and temperature are important factors that influence the performance of activated carbon and solute uptake in adsorption process. Thus, this research work was aimed at studying the effect of solution pH and temperature on phenol adsorption onto rice husk activated carbon. Results obtained showed that when pH was increased from 2 to 4, adsorption capacity and removal efficiency increased, and thereafter, decreased progressively with additional increase in pH. Results also showed that when temperature was increased from 30 to 50 oC adsorption capacity and removal efficiency decreased. Therefore, this study has established that the optimum solution pH for adsorption of phenol onto phosphoric acid modified rice husk activated carbon is 4, and better performance of the adsorption process was occurred at lower solution temperatures.